Genome-Wide Association Study Uncovers Novel Genomic Regions Associated With Coleoptile Length in Hard Winter Wheat - Sidhu, Jagdeep Singh; Singh, Dilkaran; Gill, Harsimardeep Singh; Brar, Navreet Kaur; Qiu, Yeyan; Halder, Jyotirmoy; Al Tameemi, Rami; Turnipseed, Brent; Sehgal, Sunish Kumar (Frontiers in Genetics, 2020)
Successful seedling establishment depends on the optimum depth of seed placement especially in drought-prone conditions, providing an opportunity to exploit subsoil water and increase winter survival in winter wheat. Coleoptile length is a key determinant for the appropriate depth at which seed can be sown. Thus, understanding the genetic basis of coleoptile length is necessary and important for wheat breeding. We conducted a genome-wide association study (GWAS) using a diverse panel of 298 winter wheat genotypes to dissect the genetic architecture of coleoptile length. We identified nine genomic regions controlling the coleoptile length on seven different chromosomes. Of the nine genomic regions, five have been previously reported in various studies, including one mapped to previously known Rht-B1 region. Three novel QTLs, QCL.sdsu-2AS, QCL.sdsu-4BL, and QCL.sdsu-5BL were identified in our study. QCL.sdsu-5BL has a large substitution effect which is comparable to Rht-B1’s effect and could be used to compensate for the negative effect on Rht-B1 locus on coleoptile length. In total, the nine QTLs explained 59% of total phenotypic variation. A cultivar ‘AGATE’ with the longest coleoptile length had favorable alleles at all nine genomic regions and could be valuable germplasm for wheat breeding. Gene annotations in the candidate regions revealed several putative proteins of specific interest including cytochrome P450-like, expansins, and phytochrome A. The QTLs for coleoptile length linked to SNP markers reported in the current study could be employed in marker-assisted breeding for long coleoptile in wheat. Thus, our study provides valuable insights into the genetic and biological basis of regulation of the coleoptile length in winter wheat.